2019
DOI: 10.1103/physrevlett.123.247206
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Study on Current-Induced Effect in an Antiferromagnet Insulator/Pt Bilayer Film

Abstract: Electrical control and detection of magnetic ordering inside antiferromagnets has attracted considerable interests, for the potential advantages in operating speed and device densities.In contrast to ferromagnets, where the current-induced torque on magnetic moments can be analyzed via comparison with magnetic field's influence, the quantitative investigation on the spin torque mechanism in antiferromagnets represents a greater challenge, due to the lack of a convenient, independent method for controlling Né e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 47 publications
4
105
2
Order By: Relevance
“…Furthermore, in this work, the resistance difference between high‐ and low‐resistance states is not very stable upon electrical cycling, which needs to be largely improved. On the other hand, the “saw‐tooth” shaped resistance variation in this work may not be fully induced by the antiferromagnetic spin switching as the recent experimental works47,48 found that the Joule heating itself can result in a similar resistance variation.…”
Section: Electric‐field Control Of Antiferromagnetic Spintronic Devicesmentioning
confidence: 59%
See 2 more Smart Citations
“…Furthermore, in this work, the resistance difference between high‐ and low‐resistance states is not very stable upon electrical cycling, which needs to be largely improved. On the other hand, the “saw‐tooth” shaped resistance variation in this work may not be fully induced by the antiferromagnetic spin switching as the recent experimental works47,48 found that the Joule heating itself can result in a similar resistance variation.…”
Section: Electric‐field Control Of Antiferromagnetic Spintronic Devicesmentioning
confidence: 59%
“…Despite the above intriguing resistance switching induced by external electrical currents, which have mainly contributed to electrical switching of Néel vectors in antiferromagnets, there are other reports that emphasize nonspin–orbit torque origins47 or the absence of the electrical switching of Néel vectors48 in antiferromagnets. For example, the magnetoelastic effect could be important,47 and Joule heating could be significant in current‐switched antiferromagnetic spintronic devices 48.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under a high writing current density of 10 7 A cm −2 , intense Joule heat causes irreversible changes in the device due to electromigration and magnetoelastic artifacts, which overwhelms the spin-dependent signal. [1][2][3][4] On the other hand, utilizing AFM as a spin transmission modulator is more promising. [5] For instance, it has been shown that spin current excited by thermal gradient or microwave on a ferrimagnetic insulator, usually Y 3 Fe 5 O 12 (YIG), can be significantly enhanced through the insertion of an AFM insulator layer, such as NiO and CoO.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of these microscopies is to elucidate physical mechanisms of the switching which, e.g., in CuM-nAs have been associated with the Néel vector reorientation induced by the NSOT, and with electrical or optical pulse-induced quenching into nano-fragmented domain states of the antiferromagnet 20,21 . The microscopies are also essential for disentangling potential parasitic non-magnetic contributions to the resistive switching signals, as reported in metal/antiferromagnetic-insulator bilayers 19,[22][23][24][25][26] .…”
mentioning
confidence: 99%